Teaching Listening by using Information Transfer Diagram Activity to the Seventh Grade Students of the State Junior High School 43 of Palembang - Yus Vernandes Uzer (Universitas PGRI Palembang, 2018)
Abstract The main problem of this study was “Is it effective to teach listening by using Information Transfer Diagram Activity to the Seventh Grade Students of the State Junir High School 43 of Palembang?” The objective of the study was to find out whether or not it was effective to to teach listening by using Information Transfer Diagram Activity to the Seventh Grade Students of the State Junir High School 43 of Palembang. The method of the research used in this study was pre-experimental method with pre-test-post-test one group design. Data were analyzed by using matched t-test formula. The population of this study to teach listening by using Information Transfer Diagram Activity to the Seventh Grade Students of the State Junir High School 43 of Palembang in the academic year 2016/2017 with the total 309 students. The sample investigated was 34 students of class VII.2. The sample was taken by using convenience non random sampling. Based on the result of the data analysis, it was found that to teach listening by using Information Transfer Diagram Activity to the Seventh Grade Students of the State Junir High School 43 of Palembang was effective. The findings of this study showed that the average score in the pre-test was 5.38, the highest score was 7.75 and the lowest score was 3.0 and the average score in the post-test was 7.0, the highest score was 8.75 and the lowest score was 4.75. The result of matched t-test was 8.53 which were higher than critical value (1.692). It means that the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. Keywords: Teaching, listening, information transfer diagram activity.